1987
DOI: 10.1021/ic00267a034
|View full text |Cite
|
Sign up to set email alerts
|

Copper(I) complexes with bidentate tertiary phosphine ligands: solution chemistry and antitumor activity

Abstract: the geometry of the exchange pathways, the electronic structure and anisotropy of the M and X species, and the overlap of the different metal d orbitals with those on the X04 group. Clearly, these will be very sensitive to different M and X atoms, which accounts for the variety of magnetic structures seen in these compounds and the difficulty in rationalizing them.Acknowledgment. The authors thank R. S. McLean for collecting the susceptibility data, M. W. Sweeten for technical as-sistance, and the SERC for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
77
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(79 citation statements)
references
References 1 publication
2
77
0
Order By: Relevance
“…Auranofin was shown to possess in vivo antitumor activity against P388 murine leukemia and in vitro cytotoxic potency against both B16 melanoma and P388 leukemia cells for two decades [8]. However, very recently, additional in vitro studies indicated that auranofin is able to overcome cisplatin resistance in human 4 ovarian cancer cells [9], confirming the earlier assumption that a mechanism of action different from the recognized DNA damage induced by cisplatin could underlie the cytotoxic activity of phosphine Au(I) drugs.…”
Section: Introductionmentioning
confidence: 73%
“…Auranofin was shown to possess in vivo antitumor activity against P388 murine leukemia and in vitro cytotoxic potency against both B16 melanoma and P388 leukemia cells for two decades [8]. However, very recently, additional in vitro studies indicated that auranofin is able to overcome cisplatin resistance in human 4 ovarian cancer cells [9], confirming the earlier assumption that a mechanism of action different from the recognized DNA damage induced by cisplatin could underlie the cytotoxic activity of phosphine Au(I) drugs.…”
Section: Introductionmentioning
confidence: 73%
“…The lability of copper(I) complexes in solution is well known [17]. In order to examine the solution behavior of these complexes, the 31 P NMR spectra were recorded for the complexes and the free ligand.…”
Section: P Nmr Studiesmentioning
confidence: 99%
“…8)? Such phosphine oxidation is well precedented with palladium chemistry [12c,21], and it has also been reported for copper sulfate and dppe [22].…”
mentioning
confidence: 54%